2022
DOI: 10.2147/ppa.s365348
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Non-Adherence to Medications That Affect Surgery: A Retrospective Study in Japan

Abstract: Data on risk factors for non-adherence to doctors' and pharmacists' instructions to discontinue medications prior to surgery are lacking. This study aimed to identify characteristics and risk factors for such non-adherent patients. Patients and Methods: Data (including patient age, sex, prescription medications, comorbidities, presence of roommate at home, and number of days between receiving instruction and surgery) of 887 patients who used medications affecting surgery at a university hospital from April 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 30 publications
(44 reference statements)
1
7
1
Order By: Relevance
“… 7 , 9 , 11 We also previously reported age ≥65 years as an independent risk factor for non-adherence to medications potentially affecting surgery, and the results of the subgroup analysis in this study showed similar results ( Table 3 ). 12 However, other analyses in this study did not show aged ≥65 years as a risk factor for non-adherence. ( Tables 2, 4 and S2 – S4 ).…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations
“… 7 , 9 , 11 We also previously reported age ≥65 years as an independent risk factor for non-adherence to medications potentially affecting surgery, and the results of the subgroup analysis in this study showed similar results ( Table 3 ). 12 However, other analyses in this study did not show aged ≥65 years as a risk factor for non-adherence. ( Tables 2, 4 and S2 – S4 ).…”
Section: Discussioncontrasting
confidence: 52%
“…Medications potentially affecting surgery were used as a categorical variable, with a threshold of two medications. 12 The longest discontinuation period for medications potentially affecting surgery was 14 days. Therefore, a discontinuation period of ≥15 days was considered clinically significant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A pharmaceutical assessment is conducted for patients admitted for elective surgery after pre-admission evaluation, which is throughout the whole process of ERAS. The key points of preoperative pharmaceutical care include (1) Preoperative medication education for patients; (2) The review of prescriptions based on outpatient pharmacy pre-assessment records to ensure high adherence to medication reconciliation [ 109 ]; and (3) For high-risk cases in preoperative assessment, individualized drug intervention plans are recommended to the ERAS treatment team before surgery to optimize ERAS medication treatment [ 106 , 110 ].…”
Section: Workflow and Work Path Of Medication Treatment Managementmentioning
confidence: 99%